ANALISIS ARUS KAS OPERASI DAN LABA BERSIH TERHADAP LIKUIDITAS PADA PT BESMINDO MATERI SEWATAMA - Tamara Septian Dari; Sri Wardany; Murni Dahlena Nasution (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2021)
This study aims to determine the analysis of operating cash flow and net profit on liquidity at PT. Besmindo Material Sewatama. This study uses a quantitative descriptive approach, aiming to determine the relationship between two or more variables. The population of this research is the financial statements of PT. Besmindo Materi Sewatama during 2017-2019 multiplied by 12 months so that the population of this study was 36 months. The sample of this study uses the entire population, namely l operating cash flow statements and income statements for 36 months from 2017-2019. The analysis technique used is multiple regression analysis. The suitability test using the t test and F test was conducted to test the effect partially and simultaneously between the independent variable and the dependent variable with the assumption that other variables are considered constant. The results of the analysis obtained that the t value for the Operating Cash Flow (X1) variable was 6.533 when compared to the t table value of 1.69236. Then the calculated T obtained is greater than the T table value or 6.533 > 1.69236 then it is also seen that the sig value is smaller than the probability value of 0.05 or 0.000 < 0.05. So it can be concluded that the operating cash flow variable has an effect on liquidity. The results of the analysis obtained that the t value for the Net Profit (X2) variable was 0.611 when compared to the t table value of 1.69236. Then the calculated T obtained is smaller than the T table value or 0.611 < 1.69236 then it is also seen that the sig value is greater than the probability value of 0.05 or 0.545 > 0.05. So it can be concluded that the Net Profit variable has no effect on Liquidity. Based on the simultaneous test (f test), the calculated f value is 21,513 with a sig level of 0.000, therefore the sig value is 0.000 <1 0.05 and the calculated F value is 21,513 > F table 2.79. This shows that Ha is accepted so it can be concluded that the independent variable X1 and X2 simultaneously affect the dependent variable Y. Based on the coefficient of determination test the value of R square is 0.566. This means that the effect of variable X on variable Y is 56.6%, while the remaining 0.434 or 43.4% is influenced by other variables not included in this study.